Information Technology Based Learning Media In Increasing Interest In Learning Aqidah Akhlak - M. Ilyasa Ramadhan (AR-RASYID : Jurnal Pendidikan Agama Islam, 2023)
This study aims to describe the application of learning media in increasing the interest in learning Aqidah Akhlak for students of MTs Aisyiyah Binjai. This type of research is descriptive qualitative research. Data is obtained through observation, interviews, and documentation. The results showed that the use of audio-visual learning media is very supportive in learning activities, especially in learning Aqidah Akhlak. The pesetas students are very motivated when the learning uses the laptop/computer media, projector/LCD, and internet speaker network. In addition, the use of learning media in MTs Aiyiyah Binjai has an important role in student learning interests, including feelings of joy and increased interest in the material. The implication of this study is that the teacher in delivering the learning material in the classroom must be clever in choosingthe right media, the teacher must have creative and innovative ideas so that the learning atmosphere of students is more motivated and motivated.